On the Hamiltonicity of Timbral Graphs - Cardoso, Luan S.; Cerioli, Márcia R.; Viana, Petrucio (Anais do Encontro de Teoria da Computação (ETC); 2025: Anais do X Encontro de Teoria da Computação, 2025)
We study the existence of a Hamiltonian cycle in timbral graphs, presenting a complete characterization of which timbral graphs are Hamiltonian.